Effectiveness of Arabic Learning in Vocational School on the Mecors Assessment Scale - Tuti Qurrotul Aini; Maziya Rosyada; Zulfa Kamilatun Nuha; Inayah Inayah (Universitas Islam Negeri Walisongo Semarang - Indonesia, 2023)
This research stems from the urgency of effectiveness in learning Arabic as a foreign language for students in Indonesian schools. The learning design aims to achieve pre-set competencies and goals, thus ensuring effective learning. The purpose of this research is first to know the implementation of Arabic language learning at SMK Islamic Center Baiturahman Semarang and second to know the effectiveness of Arabic language learning at SMK Islamic Center Baiturahman Semarang in terms of process and results. The type of research conducted is field research with an analytic descriptive qualitative approach. We conducted the study at SMK Islamic Center Baiturahman Semarang. Data were collected using observation, interview, test, and documentation methods. Data analysis involves making field notes and giving codes; collecting, sorting, classifying, synthesizing, summarizing, and indexing data; providing interpretation so that the data categories have meaning; looking for and suggesting patterns and relationships; and making general findings. The findings of this study are the implementation of Arabic language learning at SMK Islamic Center Baiturahman, which refers to the curriculum used and follows the process standards even though it could be better. According to the MECORS rating scale, the effectiveness of integrated learning is quite adequate based on teachers' basic teaching skills. The prerequisites of effective learning according to Al-Khuliy's criteria in the category are well met.